2010
DOI: 10.1103/physrevc.82.024910
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of shock waves in the relativistic Riemann problem: A comparison of viscous fluid dynamics to kinetic theory

Abstract: We solve the relativistic Riemann problem in viscous matter using the relativistic Boltzmann equation and the relativistic causal dissipative fluid-dynamical approach of Israel and Stewart. Comparisons between these two approaches clarify and point out the regime of validity of second-order fluid dynamics in relativistic shock phenomena. The transition from ideal to viscous shocks is demonstrated by varying the shear viscosity to entropy density ratio η/s. We also find that a good agreement between these two a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
100
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(112 citation statements)
references
References 57 publications
(59 reference statements)
11
100
1
Order By: Relevance
“…These results are consistent with an investigation based on an AdS/CFT calculation [13] and a hydrodynamic model [14,15]. The comparison with the latter publications proofs once more BAMPS can model a hydrodynamic expansion [16,17]. Using the same non-expanding scenario, we studied the effect of dissipation in box scenario [12] and found that dissipation tends to destroy any Mach cone signal.…”
Section: Introductionsupporting
confidence: 77%
“…These results are consistent with an investigation based on an AdS/CFT calculation [13] and a hydrodynamic model [14,15]. The comparison with the latter publications proofs once more BAMPS can model a hydrodynamic expansion [16,17]. Using the same non-expanding scenario, we studied the effect of dissipation in box scenario [12] and found that dissipation tends to destroy any Mach cone signal.…”
Section: Introductionsupporting
confidence: 77%
“…In hydrodynamical approach, the centrality dependent elliptic flow suggest [29,30] Kn ≈ 0.3 and 0.5 for the central and a semi-central AuAu events, respectively. A good agreement between the Boltzmann equation for dilute system and the relativistic dissipative fluid dynamics, the main tool to study the space-time evolution of the bulk matter formed in the relativistic heavy-ion collisions at RHIC, is established [31][32][33] for Kn< 0.5.…”
Section: Resultsmentioning
confidence: 99%
“…In the latter, particles can only interact with the walls of the simulation space but not with each other and λ can therefore be regarded as infinitely large. While mean free path studies have been performed for the Sod test [7,90], where results are compared to viscous hydrodynamic simulations, we are not aware of similar work that applied either the Noh or the Sedov problem. The setup and initialization of all tests is the same as in the continuum regime described in sections IV B, IV C, and IV D, whereas for the output we only analyze the spatial profiles of n, v, p, and T .…”
Section: Study Of Non-equilibrium Systemsmentioning
confidence: 99%
“…This is currently done in a Newtonian formalism but can be extended to a relativistic regime [6][7][8][9]72].…”
Section: Minimum Distance Between Final Collision Partnersmentioning
confidence: 99%
See 1 more Smart Citation